ANALISIS PENERAPAN KURIKULUM MERDEKA PADA PEMBELAJARAN EKONOMI KELAS XI SMA NEGERI SEKABUPATEN BONE BOLANGO - Faiza Paputungan; Melizubaida Mahmud; Fatmawaty Damiti; Meyko Panigoro; Sudirman Sudirman (STKIP Persada Khatulistiwa Sintang, 2026)
This study aims to analyze the implementation of the Independent Curriculum in Economics learning for class XI in State Senior High Schools throughout Bone Bolango Regency and to identify the factors that influence it. The research method used is qualitative with a Narrative Inquiry approach. Data collection techniques were carried out through interviews, observation, and documentation in several State Senior High Schools in Bone Bolango Regency. The results of the research show that the implementation of the Independent Curriculum in Economics learning in State Senior High Schools throughout Bone Bolango Regency has been carried out quite well for the last three years. However, there are still many things that need to be improved, such as the availability of resources. Most teachers have not been able to maximize learning effectively due to a lack of understanding and training on the concept of the Independent Curriculum, as well as mastery of technology that supports digital-based learning. In addition, the lack of adequate facilities and infrastructure as well as relevant learning resources are also obstacles. Factors that influence the implementation of the Independent Curriculum include supporting factors such as teacher training and assistance as well as the availability of resources, and inhibiting factors such as facilities and infrastructure, the involvement of schools, teachers, students, and parents.